KONSEP FUTURISTIK BILIK ASMARA BAGI NARAPIDANA - JT Pareke (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2019)
The results of the study done in the Correctional Institution conducted by the Center of the Study and Development of Kemenkumham Policy for 3 months (4 May-6 August 2009) in 6 Provinces throughout Indonesia, found that the deviation of prisoners' sexual behavior varies greatly from object to object. The study was conducted to 326 prisoners, 108 respondents consisting of Head of Prison, Head of Coaching, Head of Security and discipline, head of coaching and education, and Guardian Prisoners, and 22 people including prisoners' families showed the results: 81 percent or 264 prisoners said they felt uncomfortable when their biological needs are not fulfilled. There are 78 percent or 244 prisoners often fantasize of sex, 171 prisoners or 57 percent masturbate and 52 percent or 169 prisoners conduct deviant sexual activities. The above problems show a very different situation from the good and ideals objectives initiated by Sahardjo since the beginning of the establishment of a Correctional institution as an institution of guidance, ethics, and honor. The two cases above have shown enough that sexual deviations that occur in prisons are in a very alarming stage. Given that the main correctional function is as a process of fostering prisoners when reintegrating with social societies The research method uses doctrinal research methods, which are preliminary studies using a literary approach, in the form of secondary data consisting of primary, secondary and tertiary legal materials. The author finds facts of sexual deviation and the concept of sexual rights in a Human Right perspective, the author argues that futuristic concept of romance room, the state must fulfill and protect it in the context of prisoners' protection. Reformulation in question without the need to change Law No. 12 the year 1999 as the basis of the arrangement, because if the choice is taken as we can understand together that normatively legal politics requires a long time and process. concept of the provision of romance spaces in correctional institutions can use the choice of legal products of Government Regulation as stated in Article 14 verse (2) of Law No. 12 the year 1995.Keywords: Futuristic, Romance Room, Prisoners.